2016
DOI: 10.1111/jth.13402
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis by chemically modified coagulation factor Xa

Abstract: SummaryBackground-Enzymatic thrombolysis carries the risk of hemorrhage and re-occlusion must be evaded by co-administration with an anticoagulant. Toward further improving these shortcomings, we report a novel dual-functioning molecule, Xai-K, which is both a non-enzymatic thrombolytic agent and an anticoagulant. Xai-K is based on clotting factor Xa, whose sequential plasminmediated fragments, FXaβ and Xa33/13, accelerate the principal thrombolytic agent, tissue plasminogen activator (tPA), but only when loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…We have reported that irreversible modification of the active site with chloromethyl ketones (CMKs) prevents Xa33/13 production (Fig. C), allowing the persistence of t‐PA cofactor function in plasma . The current study addresses the hypothesis that, like CMK‐modified FXa , direct oral anticoagulants (DOACs) specific for the FXa active site (rivaroxaban and apixaban) enhance fibrinolysis by stabilizing FXaβ.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…We have reported that irreversible modification of the active site with chloromethyl ketones (CMKs) prevents Xa33/13 production (Fig. C), allowing the persistence of t‐PA cofactor function in plasma . The current study addresses the hypothesis that, like CMK‐modified FXa , direct oral anticoagulants (DOACs) specific for the FXa active site (rivaroxaban and apixaban) enhance fibrinolysis by stabilizing FXaβ.…”
Section: Introductionmentioning
confidence: 92%
“…Positioned at the convergence of the intrinsic and extrinsic branches of coagulation, the activated form of factor X, FXa, is an important target for drug development . FXa is localized to the site of vascular damage by calcium‐dependent association with the cofactors activated FV and anionic phospholipid‐containing membrane (PL), where it converts prothrombin to thrombin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations